Development of perceived prenatal maternal stress scale - P Sreeja Gangadharan; S P K. Jena (Wolters Kluwer Medknow Publications, 2019)
Background: Pregnancy is a state, which is often associated with extreme joy and happiness. Women undergo a number of physiological and psychological changes during pregnancy, which are often stressful if aligned with other adverse life events, compromising their health and well-being. However, there exists no comprehensive psychological instruments for measuring this stress. Objectives: The study was conducted to develop a multidimensional scale to assess prenatal maternal stress (PNMS) comprehensively. Methods: The initial phase of the study focuses on developing items and assessing the content validity of these items. The second phase focuses on pilot-testing and field-testing the newly developed perceived PNMS scale (PPNMSS) among 356 pregnant women belonging to different parity and trimester from November 2015 to October 2016. Results: The underlying factor structure of the 28-item PPNMSS had explored using exploratory factor analysis. The final scale is retained with 15 items having considerable item loading under four major factors as follows: perceived social support, pregnancy-specific concerns, intimate partner relations, and financial concerns. Reliability of each of these dimensions was assessed using Cronbach's alpha. Convergent and divergent validity of the scale was assessed by correlating the scores with perceived stress scale and the World Health Organization (five) well-being index (1998 version). Conclusions: As a comprehensive scale, PPNMSS is efficient to measure PNMS, which facilitates an early detection of stress and depression among pregnant women and timely intervention by health care professionals.